2014
DOI: 10.1002/nur.21573
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Causal Model of Agitation Among Institutionalized Residents With Dementia in Taiwan

Abstract: The aim of this study was to test a causal model of the predictors of agitation among 405 nursing home residents in Taiwan with varying degrees of cognitive impairment. Chart review and behavioral observations were used to assess residents' physical and psychosocial condition. The final version of the model had a good fit. Cognitive function and depression had direct effects on agitation, and pain and functional ability had indirect effects on agitation via depression. Additionally, cognitive function and pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…That is, enhanced ADL performance indirectly mitigates agitated behaviours by improving cognitive function and reducing depression. This result is similar to the findings reported by Chen, Lin, Chen, and Liu (), in which ADL could indirectly improve agitation by improving depression.…”
Section: Discussionsupporting
confidence: 92%
“…That is, enhanced ADL performance indirectly mitigates agitated behaviours by improving cognitive function and reducing depression. This result is similar to the findings reported by Chen, Lin, Chen, and Liu (), in which ADL could indirectly improve agitation by improving depression.…”
Section: Discussionsupporting
confidence: 92%
“…This can be supported by Miu and Chan (2014) who found that 15% of the patients who had pain also had the presence of depression compared to 8.4% of the patients without pain. Furthermore Chen et al (2014) found a direct association between depression and agitation, and pain was identified to affect agitation via depression. This suggests that pain, depression and agitation could be connected and this would need to be considered when assessing patients, also that further research needs to be undertaken to see the links between depression and pain and agitation.…”
Section: Pain and Behaviourmentioning
confidence: 96%
“…Three of the papers (Miu and Chan 2014;Chen et al 2014;Husebo et al 2014) looked at whether pain was associated with depression and agitation, and discovered an association between pain agitation and depression. Husebo et al (2014) considered if pain treatment affected mood in patients with dementia.…”
Section: Pain and Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of SEM (and other related causal analysis approaches) is rapidly expanding in epidemiology [ 9 , 16 ]. Emerging areas particularly include occupational exposure assessment [ 17 ], multiple determinants of single disease exposures [ 18 , 19 ], behavioral studies linked to disease [ 20 ], environmental determinants of disease [ 21 ], and non-transmissible diseases [ 22 ]. The application of SEM to study co-infection remains rare [ 23 25 ], but can be used to examine relationships among measured variables (pathogens) without requiring a priori knowledge of pathogen exposure order.…”
Section: Introductionmentioning
confidence: 99%